Interleukin-1 in cerebrospinal fluid for evaluating the neurological outcome in traumatic brain injury. Issue 4 (12th April 2019) - Yue, Yingming; Shang, Chongzhi; Dong, Huajiang; Meng, Kun
Abstract : Objective Severe traumatic brain injury (TBI) is associated with unfavorable outcomes secondary to injury from activation of the inflammatory cascade, the release of excitotoxic neurotransmitters, and changes in the reactivity of cerebral vessels, causing ischemia. Inflammation induced by TBI is complex, individual-specific, and associated with morbidity and mortality. The aim of the present study was to discover the differentially expressed cerebrospinal fluid (CSF) proteins and identify which can improve the clinical outcomes in TBI patients. Methods In the present study, we reported 145 patients with TBI and found the change in patients' leukocytes in serum and interleukin-1 (IL-1) in CSF, which strongly correlated with the neurological outcome. In terms of results of leukocytes in blood and IL-1 in CSF, we retained the patient's CSF specimens and conducted a proteomic analysis. Results A total of 119 differentially expressed proteins were detected between samples of TBI and the normal, which were commonly expressed in all samples, indicating the differentially expressed proteins. When the patients' Glasgow outcome score (GOS) improved, IL-1 was down-regulated, and when the patients' GCS score deteriorated, IL-1 was up-regulated accompanied with the progression in TBI. Conclusion The differentially expressed proteins in CSF may be the novel therapeutic targets for TBI treatment. The leukocytes in blood samples and the IL-1 in CSF may be two important indicators for predicting the prognosis of TBI patients.